Limits to decolonization: Indigeneity, territory, and hydrocarbon politics in the Bolivian Chaco. Issue 3 (November 2019) - Anthias, Penelope; Correia, Joel E.; McEwan, Cheryl; Bryan, Joe; Anthias, Penelope
This book review symposium critically evaluates Penelope Anthias' recent text Limits to Decolonization: Indigeneity, Territory, and Hydrocarbon Politics in the Bolivian Chaco (Cornell University Press 2018). Through deep ethnographic attention, Anthias' text evaluates Indigenous struggles for territory in the context of "post-neoliberal" Bolivia under the Evo Morales administration, showing the variegated and nuanced politics of autonomy in an era of hydrocarbon extraction and increasingly contradictory state-Indigenous relations. The text examines the "limits" of rights and state-led territorial titling processes to radically challenge the racialized extractive geographies that shape the Bolivian Chaco region. In so doing, Anthias' ethnography provides a rich analysis of how Guaraní Indigenous peoples are reshaping their relations with non-Indigenous landowners and the hydrocarbon industry to advance new forms of territorial autonomy and self-determination with significant ramifications on Indigenous studies in Latin America. This book review symposium draws from a session at the 2019 American Association of Geographers Conference, featuring two leading geographers who share their critical readings of Limits to Decolonization with a conclusion by Anthias that responds to the written reviews.